Inovasi desain keramba untuk budidaya tiram dalam meningkatkan ekonomi masyarakat pesisir di Gampong Cot Seurani, Kabupaten Aceh Utara (Innovation of cage design for oyster cultivation on improving the economy of coastal communities in Cot Seurani Village, Aceh Utara District) - Imamshadiqin, Imamshadiqin; Erniati, Erniati; Muliari, Muliari; Salmarika, Salmarika; Ruzanna, Arina; Imanullah, Imanullah; Fikri, Rizalul; Sitanggang, Hizrah Ayumi (Universitas Syiah Kuala, 2023)
Cot Seurani Village is one of the coastal villages in Muara Batu District, North Aceh Regency which has fisheries and marine potential that can be used as oyster cultivation land. The people in Cot Seurani Village predominantly work as fishermen, the potential of existing oysters has not been utilized optimally, they still collect them directly from nature, such as on rocks at TPI and its surroundings. The aim of this service activity is to introduce, socialize and directly practice the innovation of oyster cages which can be used as oyster cultivation business land in Cot Seurani Village, North Aceh in order to encourage oyster farmers to open oyster cultivation businesses independently and in a measurable manner using economical materials. The stages of this activity include program planning, preparation, socialization on making oyster cages, lowering oyster cages into the sea and monitoring and evaluating to publishing the results of the service in print media and scientific journals, as well as making reports on the results of the service. The final result, in the form of samples of oyster cage products that have been lowered into the sea, can be used by oyster farmers as an environmentally friendly oyster cultivation area to facilitate the production process and improve the welfare of oyster farmers in Cot Seurani Village.